DUKUNGAN EMOSIONAL PERAWAT DAPAT MENURUNKAN TINGKAT KECEMASAN PADA PASIEN PRE OPERASI MAYOR DI RUANG MULTAZZAM RUMAH SAKIT ISLAM SITI HAJAR MATARAM - Maelina Ariyanti; Heri Bahtiar; Zuliardi (LPPM STIKES Mataram, 2024)
Introduction: Surgery or surgery is an invasive action by opening the body tissue. Data from the Indonesian Demographic and Health Survey, states that the incidence of major surgery in Indonesia continues to increase, namely 1.2 million people or an increase of 10% from the previous year. At RSI Siti Hajar Mataram, until November 2023, there were 486 surgeries and 97 of them came from the Multazzam inpatient room. Before undergoing surgery, patients often experience various forms of fear and anxiety which are normal psychological responses. These negative perceptions include apprehension about the anesthesia process, fear of the pain that may occur due to the surgical wound, and a sense of insecurity arising from ignorance about the procedure itself. In addition, patients may also feel anxious about potential deformities that may affect their self-image and quality of life after surgery. Objectives: This study aims to determine the relationship between nurse emotional support and anxiety levels in major preoperative patients in the Multazzam Room, Siti Hajar Islamic Hospital. Methods: This type of research is a type of analytic survey research with a cross sectional approach. The population in this study were 97 respondents with a sample of 19 respondents. Data analysis using the Spearman-Rho test. Results: Based on the results of statistical test analysis using Spearman Results: Based on the results of statistical test analysis using Spearman-rho, it was found that the significance value between nurse emotional support and anxiety level of preoperative patients, P value 0.00 <0.05. So it can be concluded that there is a significant relationship between the emotional support of nurses and the anxiety level of major preoperative patients in the Multazam Room of RSI Siti Hajar Mataram.The role of nurses is important for patients as service users in nursing services which will help one of the processes of the patient's recovery itself. Nurses have an important role that includes giving special attention to patients and families, actively asking questions, communicating gently, providing support, being responsive, skilled, respecting patients, and delivering explanations well. With this, patient trust will arise and can reduce the level of anxiety experienced before treatment. Conclusion: Thus, the better the nurse's emotional support, the lower the level of pre-major surgery anxiety.